Political Information Sharing through Facebook: A survey of Pakistani Netizens - Humera Akhtar; Dr. Nosheen Fatima Warraich; Dr. Khalid Mahmood; Muhammad Sajid (Journal of Political Studies, 2021)
People engage in online political debates through Facebook and online political information sharing leads to offline political participation. This study aims to analyse the use and influence of Facebook on the information-sharing practices of Pakistani netizens. A quantitative research design based on an online questionnaire survey was used to collect data from Pakistani netizens who were also active users of Facebook. Data showed that the majority of the respondents positively used Facebook during an election to enhance their political knowledge and participation. They also forwarded political information and influenced their friends to vote for a specific candidate in the election. The Facebook campaign had a positive influence on election results as well as the turnout of the election. Findings also revealed that demographic factors of respondents did not have any effect on their information sharing practices during a general election. Moreover, caution should be exhibited to avoid posting derogatory and appalling comments and fake news. The use of Facebook among educated netizens in the Pakistani General election may fill the gap in the psephology and context of a developing country. Findings may apply to other developing countries with similar contexts.